Predictive value of low protein concentration in cirrhotic ascitic fluid as a risk factor for occurrence of spontaneous bacterial peritonitis - Entanuos, Melad; Dogman, Dad; Shamat, Akram (Latakia University Journal -Medical Sciences Series, 2020)
Introduction : Spontaneous bacterial peritonitis (SBP) is a serious common bacterial infection in patients with cirrhosis and ascites requiring prompt recognition and treatment. Aim : The aim of the present study was to evaluate the frequency, possible risk factors and the role of low ascitic protein concentration in the development of first time SBP. Materials and Methods : A total of 78 cirrhotic ascetic patients admitted to Tishreen and Al- Assad University Hospitals in Lattakia , Syria , between February 2017 and February 2017 were enrolled in this study . SBP peritonitis was diagnosed through history-taking , physical examination and laboratory investigations, including ascetic fluid study and the detection of ascites total protein level. Results : Of the 78 cirrhotic patients, SBP was diagnosed in 20 (25.6%); in total, all the patients had single episode of SBP. Among the studied clinical and laboratory variables, we found association between SBP and low ascetic protein level (P=0.0002) , the low platelet count (P <0.0001), higher bilirubin concentration (P = 0.03) . Only low protein in ascites less than or equal to 1g/dl was a predictor of SBP (OR:16.3, 95%CI: 4.7-56.2) . Conclusion : In our study, the frequency of first-episode SBP was 25.6 % . Low platelet count, high bilirubin concentration , low ascetic protein content were the predictors for the development of SBP; only low protein in ascites less than or equal to 1 was independent predictors of SBP. القيمة التنبؤية لانخفاض بروتين سائل الحبن التشمعي كمشعر خطر لحدوث التهاب الصفاق الجرثومي العفوي مقدمة : التهاب الصفاق الجرثومي العفوي Spontaneous Bacterial Peritonitis(SBP) هو انتان جرثومي خطير و شائع عند مرضى التشمع مع حبن و يتطلب تشخيصاً سريعاً و علاجاً فورياً . الهدف : الهدف من هذه الدراسة هو تحديد مرضى سائل الحبن التشمعي الذين سيحدث لهم التهاب الصفاق الجرثومي العفوي بناء على معرفة العلاقة بين تركيز بروتين سائل الحبن التشمعي المنخفض وحدوث التهاب الصفاق الجرثومي العفوي بغية وضع المريض المؤهب على علاج وقائي بالصادات الحيوية وتجنيبه المضاعفات والاختلاطات الخطيرة لالتهاب الصفاق الجرثومي العفوي . المواد و الطرق : شملت هذه الدراسة 78 مريض تشمع مع حبن قُبلوا في مشفيي تشرين و الأسد الجامعيين , اللاذقية , سورية , في الفترة الممتدة من شباط 2016 حتى شباط 2017 . تم تشخيص التهاب الصفاق الجرثومي العفوي (SBP) من خلال أخذ القصة المرضية , الفحص السريري , الاستقصاءات المخبرية بما في ذلك تحليل سائل الحبن و قياس تركيز البروتين فيه. النتائج : من بين 78 مريض تشمع مع حبن تم تشخيص SBP عند 20 مريض (25.6%) و جميع هؤلاء المرضى يحدث لديهم SBP للمرة الأولى . من بين المتغيرات السريرية و المخبرية التي درست وجدنا ترافق حدوث التهاب الصفاق الجرثومي العفوي مع تركيز بروتين سائل الحبن المنخفض (P=0.0002) تعداد الصفيحات المنخفض (P<0.0001) , تركيز البيلروبين المصلي المرتفع (P=0.03). لا علاقة بين استخدام المدرات أو PPIs و حدوث SBP . تركيز البروتين الكلي في سائل الحبن ≤ 1 غ/دل كان عامل خطر لحدوث SBP عند مرضى التشمع مع حبن . الخلاصة : في دراستنا , معدل حدوث النوبة الأولى من التهاب الصفاق الجرثومي العفوي عند مرضى التشمع مع حبن هو 25.6% . يترافق حدوث SBP مع تركيز بروتين سائل الحبن منخفض , تعداد صفيحات منخفض في الدم المحيطي, وتركيز بيليروبين المصلي مرتفع . انخفاض تركيز بروتين سائل الحبن ≤ 1 غ/دل هو عامل خطر لحدوث SBP (4.7-56.2 95%CI:. OR:16.3).